THE ISSUE OF LINGUISTIC ADAPTATION OF UKRAINIAN LAMENTS AS ELEMENTS OF RITUAL FOLKLORE IN FILM TRANSLATION INTO KOREAN - АЛІМЕНКО, Ольга; ТОГОБИЦЬКА, Анна (Current Issues of Foreign Philology, 2025)
The article is devoted to the study of the peculiarities of translating Ukrainian laments into Korean in film translation. Laments, as a genre of ritual folklore, hold significant ritual and emotional value, which complicates their transmission in a foreign-language context. The study examines the main challenges of adapting laments for a Korean-speaking audience, particularly the lexical-syntactic and communicative-pragmatic features of their reproduction. Preserving the cultural authenticity and emotional impact of laments in film translation requires considering not only linguistic equivalents but also the specifics of mourning discourse in Korean culture. An essential aspect is the adaptation of stylistic devices such as metaphors, repetitions, diminutive forms, and rhetorical questions that convey the depth of grief and the tragic nature of the moment. The article analyzes the translation of selected laments from the film «Dovbush» (2023) and their representation in the official Korean subtitles. The study revealed that the process of translating laments involves various translation transformations, including rearrangement, omission, paraphrasing, semantic expansion, and the adaptation of culturally marked elements. Notably, the Korean translation often alters the emotional emphasis of the original texts, softening or modifying the tragic motifs. This is influenced by both linguistic and pragmatic factors, particularly differences in the perception of mourning-related vocabulary in Ukrainian and Korean cultures. The findings highlight the necessity of carefully selecting expressive means in film translation to preserve both the semantic and emotional aspects of laments as much as possible. The study’s conclusions may be useful for translators working with folklore texts, as well as for further research in the field of audiovisual and intercultural translation.